Hacia la construcción de una narrativa estratégica de competitividad: visión sobre el futuro del Oriente antioqueño a partir del diseño y ejecución del Fondo Empresarial Agroindustrial 2016-2019 = Towards the construction of a strategic narrative of competitiveness: vision on the future of Eastern Antioquia based on the design and implementation of the Agroindustrial Business Fund 2016-2019 (2018)
Faced with the scenario of governing with the public, with citizens who deliberate, nowadays public administration requires that the analysis of projects included in development plans, as well as those of public policies, apply theoretical and methodological techniques and instruments that transcend the evaluation of formulation and results. In this work, we take up an epistemological and constructivist that privileges rhetoric in the process of designing proposals that respond to public problems, granting public problems, giving relevance to the reality understood as a social construction, through the as a social construction, through narration, and relative, since each actor can observe it differently. may observe it in a different way. A general description is given of the main results of the institutional and social participatory exercise of constructing a subregional narrative based on the following a subregional narrative based on the identification of strengths and challenges of eastern Antioquia in the area of agriculture and livestock. Antioquia in terms of agriculture and livestock after the implementation of the Agroindustrial Business Fund "Antioquia". Agroindustrial Business Fund "Antioquia Siembra". To this end, the Critical Discourse Analysis (Fischer) is proposed as a basis for the recognition of the reality of different actors, with homogeneous or dissimilar different actors, with homogeneous or dissimilar identities and evaluations, as contributors to public to public management in the strengthening of the competitiveness of this sector